Political Communication Strategies in the 2024 Solo Mayoral Election: The Case of Respati-Astrid - Herning Suryo Sardjono; Silvi Aris Arlinda (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Political communication media play a crucial role in shaping public opinion and influencing voter behavior in contemporary electoral contests. However, limited studies have specifically examined how non-traditional political candidates strategically integrate multiple communication media to achieve electoral success in local elections. This study aims to analyze the utilization of political communication media by the Respati-Astrid candidate pair in the 2024 Solo Mayoral Election. The research employs a descriptive qualitative approach, with data collected through interviews, documentation, and media analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that the Respati-Astrid campaign implemented an integrated political communication strategy through the combination of outdoor media, digital media, interpersonal communication, and mass media. Outdoor media such as billboards were used to strengthen visibility and political branding, while digital platforms including Instagram, TikTok, and YouTube effectively expanded outreach and engagement among younger voters. Interpersonal communication through blusukan activities enhanced emotional connection and public trust, whereas mass media reinforced political legitimacy and public narratives. The study demonstrates that the convergence of multiple communication channels, combined with audience-oriented messaging, contributed significantly to the candidates’ electoral success. This research contributes to political communication studies by providing empirical evidence on the importance of integrated media strategies and adaptive communication approaches in local electoral politics in Indonesia.